The Effect of Education, Workforce, Economic Growth and Labor Force Participation Rate on City Labor Absorption in Aceh Province, Indonesia - Mulyani, Desi; Sartiyah, Sartiyah; Srinita, Srinita (International Journal of Advances in Social Sciences and Humanities, 2023)
The Labor Force Participation Rate (LFPR) provides an overview of the population aged 15 years and over who are active at working age, whether they are currently working, not yet working, or looking for work. By knowing the LFPR, the percentage of the working-age population that is economically active in a region can be known. The higher the LFPR, the higher the supply of available labor to produce goods and services. This study aims to analyze the effect of education, junior and senior high school workforce, economic growth, and labor force participation rates on employment absorption in the districts/cities of Aceh Province. The data used is secondary data with a time series from 2014 to 2021 and cross-sections from 23 districts/cities in Aceh Province. Data analysis used the Panel Regression Model with the Generalized Least Squares Method. The results showed that the workforce has a junior high school education, the average length of schooling, and the labor force participation rate positively affect employment. In contrast, the workforce has a high school education, and economic growth does not affect employment. Considering that the number of junior high school education staff is the largest, educational improvement must be carried out with government policies in remote areas in Aceh Province so that more highly educated workers can be absorbed.